Structured Reporting in Radiology Residency: A Standardized Approach to Assessing Interpretation Skills and Competence - Denise Castro; Siddharth Mishra; Benjamin Y. M. Kwan; Muhammad Umer Nasir; Alan Daneman; Donald Soboleski (International Medical Education)
The field of radiology heavily relies on image interpretation and reporting. Radiology residents undergo evaluations primarily based on their interpretation skills, often encountering varied cases with differing complexities. Assessing resident performance in such a diverse setting poses challenges due to variability in judgment among assessors. One aspect of training that can be standardized is the reporting process. Developing a structured reporting system could aid in evaluating resident milestones and achievement of Entrustable Professional Activities (EPAs), facilitating standardized assessment and comparison among peers. From our experiences, we describe a logical reasoning pathway followed by residents in their training, progressing from recognizing abnormalities to describing findings, identifying associated positive and negative findings, and recommending appropriate management. Each step provides evidence of milestone achievement and can be assessed through structured reporting. We propose that a grading system can be applied to assess perception skills, description accuracy, recognition of associated findings, formulation of differential diagnoses, recommendations, and consultation with clinicians. Comparison between junior and senior resident reports allows for monitoring progression and identifying areas for improvement. Although implementing this grading system poses challenges, it offers potential benefits in providing standardized assessment and guiding individualized learning curves for residents. Despite its limitations, once established, the system could enhance residency training in diagnostic imaging.